Generalizing from past successes - Haggblade, Steven (International Food Policy Research Institute, 2004)
Past successes in African agriculture can point the way to promising avenues for achieving similar success in the future. Drawing lessons from past success requires identifying a range of successful and less successful episodes and then studying and comparing them. To identify a broad range of successful episodes in African agriculture, our analytical team launched an expert survey, polling more than 1,000 African agriculture specialists. In conducting this review, we defined 'success' as: a significant, durable change in agriculture resulting in an increase in agriculturally derived aggregate income, together with reduced poverty and/or improved environmental quality. From the responses, we, together with our advisory group, selected a dozen successful episodes for in-depth review and dispatched case study teams to investigate them. Although these episodes differ widely in terms of instigators of change, points of intervention, levels of subsidy involved, food and export crops, regional diversity, duration, and scale achieved, they suggest ways in which past sucesses can be replicated and scaled up.